2014
DOI: 10.12659/msm.890721
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nano-Carbon in Lymph Node Dissection for Thyroid Cancer and Protection of Parathyroid Glands

Abstract: Background The aim of this study was to explore a new method to identify and protect parathyroid glands in neck lymph node dissection for patients with thyroid cancer. Material/Methods One hundred patients with thyroid cancer underwent total thyroidectomy combined with central neck lymph node dissection. During the operation, 50 patients receiving nano-carbon suspension were included in the experiment group, and 50 patients without nano-carbon suspension were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Hypocalcemia occurred in 5 patients of the control group (20%) and 4 patients of the test group (4%) at 1 day after surgery. No between-group significant difference was found in hypocalcemia at 1st day, which was different from the results of hypocalcemia at 48 hours after surgery reported by Luo [16]. This was because every patient immediately got calcium supplementation after total thyroidectomy, which affected the calcium serum level at 1 day after surgery.…”
Section: Discussioncontrasting
confidence: 81%
“…Hypocalcemia occurred in 5 patients of the control group (20%) and 4 patients of the test group (4%) at 1 day after surgery. No between-group significant difference was found in hypocalcemia at 1st day, which was different from the results of hypocalcemia at 48 hours after surgery reported by Luo [16]. This was because every patient immediately got calcium supplementation after total thyroidectomy, which affected the calcium serum level at 1 day after surgery.…”
Section: Discussioncontrasting
confidence: 81%
“… 39 The removal of lymph and adipose tissue may cause avascular necrosis of the parathyroid glands, which may result in hypocalcaemia in patients with TT after surgery. 40 Studies have indicated that the incidence of transient hypocalcaemia after TT is 27.5%. 41 A previous study reported that the incidence of hypocalcaemia in patients undergoing TT (38.8%) was significantly higher than that in patients undergoing lobectomy (13.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the included studies, the dose of CNs is 0.1 to 0.2 ml per point and 2–3 points around tumor within the thyroid capsule were recommended. After being properly injected, the CNs enter the lymphatic capillaries and stain lymph nodes in 10-15min, rather than PGs and the recurrent laryngeal nerve [ 10 , 13 , 18 – 20 , 27 , 32 37 ]. It is hypothesized that this technique facilitates intraoperative identification of LNs and improves thoroughness of LN dissection for thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%